6: WISCONSIN'S WILD TURKEY RESTORATION EXPERIMENT - Robert E. Dreis; Clarence F. Smith; Lewis E. Myers (Wildlife Society Bulletin)
ABSTRACT A turkey stocking experiment that used hybrids developed from crossing eastern wild turkeys (Meleagris gallopavo silvestris) with domestic turkeys, was initiated in Wisconsin in 1954. A total of 286 adult game‐farm hybrids were released in the Necedah Refuge‐Meadow Valley Wildlife Area complex of 100,000 acres. This release was followed in 1957 with a release of 425 poults raised at the State Game Farm. An outbreak of disease and a severe winter all but wiped out the population. Survivors exhibited wild characteristics and apparently, Wisconsin now has a population of turkeys sufficiently wild and adapted to environmental conditions to permit it to maintain itself. The turkey population built up to an estimated peak of 2,500 birds in the 300 square miles of occupied range in the Necedah‐Meadow Valley Area by the fall of 1966. Two years of successive brood failures and a severe winter reduced this population to less than 50 (estimated) birds. As of July 1969, the population had risen to an estimated 200 birds. A total of 67 birds were wild‐trapped and planted in four different locations in Wisconsin during 1967 and 1968. In 3 years, these nuclei have expanded to occupy a range of 220 square miles and have grown to an estimated population of 900 birds. In 1967, a release of 15 Merriam's turkeys (M. g. memiami) was made in Grant County. In 1966, 1967, and 1968, Wisconsin held spring gobbler hunts in the Necedah‐Meadow Valley Area. Kills of 20, 21, and 18 gobblers were recorded for the respective years. Hunter numbers were limited by IBM selection. Predation does not appear to be a limiting factor but, during winter stress conditions, kills by bald eagles (Haliaeetus leucocephalus), bobcats (Lynx rufus), and coyotes (Canis latrans) have been observed. One weakened turkey was killed by a red fox (Vulpes fulva).